تأثيرات أنواع التغطية المختلفة للتربة الزراعية في معدل استهلاك مياه الري من المحاصيل (محصول الفول أنموذجاً) - حسان الجودي; معن سلامة (Tishreen University, 2019)
تهدف الدراسة إلى تحديد تأثيرات التغطية المختلفة لسطح التربة المزروعة بالفول على ترشيد استهلاك مياه الري وفق العناصر التالية:1- المحتوى الرطوبي للتربة (خلال مراحل النمو). 2- الاستهلاك الرطوبي في المنطقة الجذرية (15-30) سم.(خلال مراحل النمو) 3 - الإنتاجية كغ/هكتار وكفاءة الاستهلاك المائي لتر/1كغ. تضمنت التجربة أربع معاملات مختلفة للتغطية: رقائق بلاستيكية سوداء- رقائق بلاستيكية بيضاء- من دون تغطية- تغطية بالقش). نفذت التجربة وفقاً لتصميم القطاعات العشوائية الكاملة بواقع ثلاثة مكررات لكل معامل.مساحة الوحدة التجريبية هي 2.25 م2. وقد وجدت فروقات معنوية تدل على اختلاف التأثيرات بين معاملات التغطية مقارنة مع الشاهد(من دون تغطية). .كما وجدت فروقات معنوية تدل على تأثيرات اختلاف نوعية التغطية؛ وذلك في أغلب عناصر التقييم السابقة This study aims to determine the different  influences of the soil surface covering, planted with beans on rationalizing irrigation-water consumption, in accordance with the following aspects: 1- Soil moisture content (during the growing stages). 2- Moist consumption in the root zone (15-30) cm, (during the growing stages). 3- Productivity (kg/ha) and efficiency of water consumption (L/kg). The experiment has involved four different coefficients of covering (black plastic plates, white plastic plates, without covering, straw covering). This experiment has been executed, according to the design of the total arbitrary zones, by testing each coefficient three times. The experimental unit area is 2.25m2. As a result, some significant differences have occurred, indicating the difference of the influences among the covering factors, compared to the uncovered case. There have also been significant differences, indicating influences in line with the varied covering types, in most of the previously evaluated elements.